2008
DOI: 10.1111/j.1471-4159.2008.05643.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of γ‐secretase cleavage‐region mutations on APP processing and Aβ formation: interpretation with sequential cleavage and α‐helical model

Abstract: Overwhelming evidence supports the amyloid hypothesis of Alzheimer’s disease that stipulates that the relative level of the 42 amino acid β-amyloid peptide (Aβ42) in relationship to Aβ40 is critical to the pathogenesis of the disease. While it is clear that the multi-subunit gamma secretase is responsible for cleavage of the amyloid precursor protein (APP) into Aβ42 and Aβ40, the exact molecular mechanisms regulating the production of the various Aβ species remain elusive. To elucidate the underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…These observations prompted us to determine the effect of LPA on the production of Aβ. N2a neuroblastoma cells, which stably express PS1wt and myc-tagged APPsw, have been used in many previous studies for investigating the mechanism of Aβ production [21, 23, 25]. These cells were starved in a serum-free medium for 24 h and then treated with LPA.…”
Section: Resultsmentioning
confidence: 99%
“…These observations prompted us to determine the effect of LPA on the production of Aβ. N2a neuroblastoma cells, which stably express PS1wt and myc-tagged APPsw, have been used in many previous studies for investigating the mechanism of Aβ production [21, 23, 25]. These cells were starved in a serum-free medium for 24 h and then treated with LPA.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that AICD production may be independent of Aβ given that γ-secretase has two activities, the first named ε-cleavage cuts CTFβ to Aβ45–49 and the second γ-cleavage to generate secreted Aβ of 39-43 residues (Fig 5) 19, 21 . In addition to Aβ48/49, one study identified a critical intermediate, Aβ46, in Aβ40 and Aβ42 generation and named this as ζ cleavage without attempts to detect the corresponding AICD 34 . The current study suggests that there is no AICD corresponding in size to forms other than Aβ48/49, supporting the view that they are intermediates derived from further processing of these longer Aβ forms 16, 19, 20, 3436 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Aβ48/49, one study identified a critical intermediate, Aβ46, in Aβ40 and Aβ42 generation and named this as ζ cleavage without attempts to detect the corresponding AICD 34 . The current study suggests that there is no AICD corresponding in size to forms other than Aβ48/49, supporting the view that they are intermediates derived from further processing of these longer Aβ forms 16, 19, 20, 3436 . Given a sequential cleavage pattern from Aβ48/49 to Aβ45/46 to Aβ42/43 to Aβ39/40, a slow or impaired γ-secretase will likely release the longer Aβ42/43 forms into the media rather than convert it to the shorter 39/40 forms.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that mitochondrial superoxide affects ␥-secretase, which is responsible for cleaving APP into A␤ of different lengths (34). Recently it was proposed that the ␣-helical structure of the APP transmembrane domain dictates the cleavage site for ␥-secretase, thereby determining which A␤ species is generated (35). Furthermore, oxidative stress has been shown to affect both the ␥-and ␤-secretases, thereby increasing APP processing into A␤ (36).…”
Section: Discussionmentioning
confidence: 99%